Compliance in epileptology. How to change the situation for better - N. N. Maslova; A. A. Litvinova; N. V. Yuryeva; P. S. Kovalev (Эпилепсия и пароксизмальные состояния)
The problem of low adherence to therapy in patients with epilepsy is one of the most pressing public health problems. Failure to follow the doctor's instructions leads to an increased risk of hospitalization and sudden death. Knowing the main predictors of non-compliance, the doctor is able to develop appropriate strategies to increase adherence. There are methods of improving compliance that should be actively implemented in the clinical practice of epileptologists. The article presents a review of the literature on this problem, clinical examples from the authors' practice are given.